Impact of task conflict on job satisfaction: Mediating effect of positive emotions while controlling personality traits - (:unkn) unknown (Allied Academies, 2016)
Drawing on the Theory of Affective Events (AET), the purpose of this paper is to examine the effect of mild and intense conflicts workings and its effects on job satisfaction. According to the AET (Weiss and Cropanzano, 1996) work related events causes on emotional responses and the subsequent outcomes for not only behavior but also attitudes. A positive affective event produces positive emotional events such as happiness. Also, a negative affective event, naturally, causes negative emotional response like dissatisfaction and anger. One of the most important variables of emotional characteristics is work environment; events in the work place, individual responses, behavioral drivers and attitudes. In the study, it is argued that how mild and intense conflict will influence positive emotions and what is the relationship between mild and intense conflict on group working and job satisfaction while positive emotions is a mediator. The authors collected data from 496 white collar participants working in industrial goods, service, textile, and banking and transportation sector via convenient sampling method and employed hierarchical regression modelling. At the end, this study will argue whether there is a relationship between the personality types and the type of conflict that causes positive emotions which is a reason of job satisfaction. It means that the personality types are used as variable component in the study.
Keywords: Job satisfaction; Mild and intense task conflict; Personality types; Positive emotions